Transcriptome and Metabolome Analyses Reveal Differences in Terpenoid and Flavonoid Biosynthesis in Cryptomeria fortunei Needles Across Different Seasons - Zhang, Yingting; Yang, Liwei; Yang, Junjie; Hu, Hailiang; Wei, Guangqian; Cui, Jiebing; Xu, Jin (Frontiers in Plant Science, 2022)
Cryptomeria fortunei has outstanding medicinal value because of its abundant flavonoid and terpenoid contents. The metabolite contents of C. fortunei needles differ across different seasons. However, the biosynthetic mechanism of these differentially synthesized metabolites (DSMs) is poorly understood. To improve our understanding of this process, we performed integrated nontargeted metabolomic (LC-MS and GC-MS) and transcriptomic analyses of summer and winter needles. In winter, the C. fortunei needle ultrastructure was damaged, and the chlorophyll content and Fv/Fm were significantly (p < 0.05) reduced. Based on GC-MS and LC-MS, we obtained 106 and 413 DSMs, respectively; based on transcriptome analysis, we obtained a total of 41.17 Gb of clean data and assembled 33,063 unigenes, including 14,057 differentially expressed unigenes (DEGs). GO and KEGG analyses showed that these DSMs/DEGs were significantly (p < 0.05) enriched in many biosynthesis pathways, such as terpenoids, photosynthate and flavonoids. Integrated transcriptomic and metabonomic analyses showed that seasonal changes have the greatest impact on photosynthesis pathways, followed by terpenoid and flavonoid biosynthesis pathways. In SCC needles, DXS, DXR and ispH in the 2-methyl-pentaerythritol 4-phosphate (MEP) pathway and GGPS were highly expressed and promoted the accumulation of terpenoids, especially diterpenoids. In WCC needles, 9 genes (HCT, CHS, CHI, F3H, F3'H, F3'5'H, FLS, DFR and LAR) involved in flavonoid biosynthesis were highly expressed and promoted flavonoid accumulation. This study broadens our understanding of the metabolic and transcriptomic changes in C. fortunei needles caused by seasonal changes and provides a reference regarding the adaptive mechanisms of C. fortunei and the extraction of its metabolites.